First person - Eric Clark (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Eric Clark is first author on 'Establishment and validation of an endoplasmic reticulum stress reporter to monitor zebrafish ATF6 activity in development and disease', published in DMM. Eric is a PhD student in the lab of Brian Link at the Medical College of Wisconsin, Milwaukee, WI, USA, investigating cellular stress pathways involved in neurodegeneration.